2013
DOI: 10.1073/pnas.1305519110
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of domain insertion on sequence-structure divergence in a superfold

Abstract: Although the universe of protein structures is vast, these innumerable structures can be categorized into a finite number of folds. New functions commonly evolve by elaboration of existing scaffolds, for example, via domain insertions. Thus, understanding structural diversity of a protein fold evolving via domain insertions is a fundamental challenge. The haloalkanoic dehalogenase superfamily serves as an excellent model system wherein a variable cap domain accessorizes the ubiquitous Rossmann-fold core domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…However, several studies have shown that protein-protein interactions decrease evolutionary rates, partly by decreasing the fraction of surface-exposed residues (5-9, 45). Likewise, interactions with large capping domains in the haloalkanoate dehalogenase superfamily constrain the structural divergence of their Rossman-fold core domain (46). Our observation that the OSBS family, which is primarily composed of monomers, evolved at a faster rate than related, homomultimeric families is consistent with these studies.…”
Section: Discussionsupporting
confidence: 86%
“…However, several studies have shown that protein-protein interactions decrease evolutionary rates, partly by decreasing the fraction of surface-exposed residues (5-9, 45). Likewise, interactions with large capping domains in the haloalkanoate dehalogenase superfamily constrain the structural divergence of their Rossman-fold core domain (46). Our observation that the OSBS family, which is primarily composed of monomers, evolved at a faster rate than related, homomultimeric families is consistent with these studies.…”
Section: Discussionsupporting
confidence: 86%
“…C1 cap domains are inserted after the β1 strand, while C2 cap domains are inserted after the β3 strand. In both cases, these cap domains reside above the HAD core and help form a structural pocket above the active site to generate substrate specificity 20,33 .…”
Section: Resultsmentioning
confidence: 99%
“…It should also help correct the widespread functional misannotation of these enzymes in databases. This ambitious goal is now feasible using a combination of approaches such as high-throughput substrate profiling and bioinformatic analyses, as has been done with other enzyme families (Burroughs et al, 2006; Huang et al, 2015; Pandya et al, 2013). …”
Section: Discussionmentioning
confidence: 99%